Vγ9Vδ2 T Cells as Strategic Weapons to Improve the Potency of Immune Checkpoint Blockade and Immune Interventions in Human Myeloma - Castella, Barbara; Melaccio, Assunta; Foglietta, Myriam; Riganti, Chiara; Massaia, Massimo (Frontiers in Oncology, 2018)
The advent of immune checkpoint (ICP) blockade has introduced an unprecedented paradigm shift in the treatment of cancer. Though very promising, there is still a substantial proportion of patients who do not respond or develop resistance to ICP blockade. In vitro and in vivo models are eagerly needed to identify mechanisms to maximize the immune potency of ICP blockade and overcome primary and acquired resistance to ICP blockade. Vγ9Vδ2 T cells isolated from the bone marrow (BM) from multiple myeloma (MM) are excellent tools to investigate the mechanisms of resistance to PD-1 blockade and to decipher the network of mutual interactions between PD-1 and the immune suppressive tumor microenvironment (TME). Vγ9Vδ2 T cells can easily be interrogated to dissect the progressive immune competence impairment generated in the TME by the long-lasting exposure to myeloma cellss. BM MM Vγ9Vδ2 T cells are PD-1+ and anergic to phosphoantigen (pAg) stimulation; notably, single agent PD-1 blockade is insufficient to fully recover their anti-tumor activity in vitro indicating that additional players are involved in the anergy of Vγ9Vδ2 T cells. In this mini-review we will discuss the value of Vγ9Vδ2 T cells as investigational tools to improve the potency of ICP blockade and immune interventions in MM.